Genetic divergence, path coefficient and cluster analysis of French bean (Phaseolus vulgaris) genotypes - VERMA, VEERENDRA KUMAR; JHA, ANJANI KUMAR; PANDEY, AVINASH; KUMAR, AMIT; CHOUDHURY, P; SWER, TANYA L (The Indian Journal of Agricultural Sciences, 2014)
Thirty four pole type French bean (Phaseolus vulgaris L.) genotypes were evaluated to assess their genetic variability to identify desirable ones for yield and quality traits. The genotypic variance was moderate to high for the all the 14 traits studied, which resulted in high heritability and moderate to high genetic advance values. Pod yield/plant was positively correlated with all traits except days to 50% flowering, pod diameter and vitamin C content. High heritability and genetic advance of leaf width, first flowering node, number of seeds/pod, number of pods per plant, average pod weight and dry matter content vis-a-vis their positive association and direct positive effect on pod yield per plant suggested for their improvement through simple selection method. All the French bean genotypes were grouped into five distinct clusters. An analysis of the percentage contribution of individual characters towards genetic diversity revealed that vitamin C content, number of pods/plant and dry matter content were the major characters contributing to genetic diversity in French bean. Based on the finding it can concluded that French bean genotypes exhibited a wide range of variability for most of the traits. Some genotypes possessed desirable genes for more than one characters, hence may be utilized directly or included in hybridization programme.